The Concept of al-Bay' in the Perspective of Mauḍū'ī Interpretation: Study of its relevance to technology-based transactions - Ahmad Syaichoni; Rifki Sahara (AQWAL Journal of Qur'an and Hadis Studies, 2022)
This article aims to re-understand the term al-bay where the context of the revelation of the Koran is different from the technology-based transaction model in the modern era. This article aims to answer the question of how al-Bay's understanding accordances the historical context, the understanding of the commentators and their relevance to technology-based buying and selling transactions in the modern era. These questions are discussed using the mauḍū'ī interpretation method with a library database. The approach used is historical critical. This article shows that the word al-bay' in the Qur'an indicates an effort to seek profit in worldly affairs, especially economics and an effort to seek divine pleasure as provisions for the afterlife in ukhrawi affairs. The historical meaning of al-bay is buying and selling transactions carried out by human beings prioritizing maṣlaḥat and avoiding mafsadat. Meanwhile, technology-based transactions contain al-bay values ​​if they fulfill their willingness, are useful, help each other and are not prohibited. In addition, technology-based buying and selling transactions must prioritize benefit and avoid mafsadat as the purpose of the birth of the term al-Bay in the Koran.